2019
DOI: 10.5897/ajar2017.12760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vermicompost on growth, quality and economic return of garlic (Allium sativum L.) at Haramaya District, Eastern Ethiopia

Abstract: Garlic (Allium sativum L.) is an important vegetable crop in Ethiopia. The yield of the crop is often constrained by low and unbalanced nutrient supply in the soil. This study was undertaken to assess effect of vermicompost (VC) on growth, quality and economic return of garlic variety Chelenko I during 2016 main rainy season in Haramaya University main campus, Ethiopia. The treatment consisted of four levels of vermicompost (0, 2.5, 5 and 7.5 tons ha-1) laid out in a randomized complete block design in three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Significant differences between the SL control group and the combinations with vermicompost were shown regarding mean yield (with the highest difference of 140% for SL < V50; p < 0.05) (Table 2). Kenea and Gedamu [25], while investigating the effect of vermicompost made from Lantana camara and Partinium hystrophorous with the addition of manure on selected garlic traits, showed that at increased vermicompost share from 0 to 7.5 t ha −1 , the average fresh weight of garlic increased by 9.5% compared to the control, while a 3-fold increase in the vermicompost rate (from 2.5 to 7.5 t ha −1 ) resulted in a 20% increase in A. sativum yield. A similar trend was shown in the present study, finding that the average yield of A. sativum increased as the proportion of vermicompost in the growing medium increased (V10 < V25 < V50) (Table 2).…”
Section: Analysis Of Selected Characteristics Of a Sativum Relating T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences between the SL control group and the combinations with vermicompost were shown regarding mean yield (with the highest difference of 140% for SL < V50; p < 0.05) (Table 2). Kenea and Gedamu [25], while investigating the effect of vermicompost made from Lantana camara and Partinium hystrophorous with the addition of manure on selected garlic traits, showed that at increased vermicompost share from 0 to 7.5 t ha −1 , the average fresh weight of garlic increased by 9.5% compared to the control, while a 3-fold increase in the vermicompost rate (from 2.5 to 7.5 t ha −1 ) resulted in a 20% increase in A. sativum yield. A similar trend was shown in the present study, finding that the average yield of A. sativum increased as the proportion of vermicompost in the growing medium increased (V10 < V25 < V50) (Table 2).…”
Section: Analysis Of Selected Characteristics Of a Sativum Relating T...mentioning
confidence: 99%
“…Kale et al [23] and Nethra et al [24] showed positive effects of vermicompost on ornamental plants (Callistephus chinensis) where vermicompost at a dose of 10t•ha −1 had a positive effect on plant height, number of leaves and flowers. Kenea and Gedamu [25] argue that using good quality vermicompost for fertiliser purposes is crucial to increase plant productivity while minimising negative environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of growth (10 dap), the applied vermicompost had no significant effect on all growth parameters. This condition is due to the slow release of vermicompost so that the availability of nutrient for plants lasts a long time [37]. The availability of nutrients in the soil is related to the vermicompost overhaul process that occurs.…”
Section: Effect Vermicompost Formulation Based On Soybean Husk and Cow Manure On Shallot's Growthmentioning
confidence: 99%